Efficacy of lower limb strengthening exercises based on different muscle contraction characteristics for knee osteoarthritis: a systematic review and network meta-analysis - Xiaoqing Ding; Yi Yang; Ying Xing; Qingsong Jia; Qingguo Liu; Jie Zhang; Jie Zhang (Frontiers in Medicine, 2024)
PurposeWhile strengthening exercises are recommended for knee osteoarthritis (KOA) treatment, the optimal type of muscle contraction remains unclear, with current research showing conflicting results. This network meta-analysis (NMA) aims to evaluate the efficacy of lower limb strengthening exercises based on different muscle contraction characteristics for KOA patients and provide clinical references.MethodsWe conducted the NMA following the PRISMA-NMA. A comprehensive search of five databases (PubMed, Web of Science, CENTRAL, Embase, and SPORTDiscus) up to August 2024 identified randomized controlled trials (RCTs) investigating lower limb strengthening exercises in KOA patients. Control groups included receiving usual care, only providing health education, or no intervention at all. Outcomes analyzed included pain, physical function, quality of life, and muscle strength.ResultsForty-one studies (2,251 participants) were included. Twenty-eight studies used rigorous randomization; eighteen reported allocation concealment. All had high performance bias risk due to exercise interventions. Regarding efficacy, isokinetic exercise ranked highest in pain relief (SMD = 0.70, 95% CI: 0.50–0.91, SUCRA = 82.6%), function improvement (SMD = 0.75, 95% CI: 0.57–0.92, SUCRA = 96.1%), and enhancement in muscle strength (SMD = 0.56, 95% CI: 0.34–0.78, SUCRA = 90.1%). Isometric exercise ranked highest in improving quality of life (SMD = 0.80, 95% CI: 0.28–1.31, SUCRA = 90.5%). Mixed strengthening exercise ranked lowest across all outcomes. High-frequency interventions (≥5 times/week) showed superior pain relief compared with low-frequency (≤3 times/week) for isotonic, isometric, and isokinetic exercise.ConclusionThis NMA suggests isokinetic exercise may be most effective for pain, function, and muscle strength in KOA patients, while isometric exercise benefits quality of life most. Mixed strengthening exercise ranked lowest across all outcomes. High-frequency interventions appear more effective than low-frequency ones. These findings support personalized KOA treatment, considering efficacy, accessibility, and patient-specific factors. Study biases, heterogeneity, and other limitations may affect result reliability. Future research should focus on high-quality studies with standardized protocols and analyze dose–response relationships to refine KOA treatment strategies.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42024582525, identifier: CRD42024582525.